Innovations in Shredder: A Multi-Cutting Machine (American Journal of Education and Technology, 2025)
This study focused on the design, fabrication, and performance evaluation of a shredding machine specifically developed for processing agricultural waste, including corn stalks and coconut covers. Powered by a 1440 rpm AC motor and utilizing a single-belt drive system, the machine was tested to measure its shredding efficiency and recovery rate under various material conditions. Shredding efficiency was defined as the percentage of material effectively shredded, while the recovery rate represented the proportion of useful shredded material collected. Trials conducted with corn stalks at 30% moisture content demonstrated an average shredding efficiency of 85.33% and a recovery rate of 70.33%, showcasing the machine’s consistency and reliability. For coconut covers, the shredding efficiency varied based on maturity and moisture content, highlighting the machine’s adaptability to different agricultural materials. The findings validate the shredding machine’s potential as an efficient tool for managing agricultural waste. By enabling the conversion of residues into valuable materials for composting and other applications, the machine supports sustainable practices and reduces environmental impact, offering a practical and eco-friendly solution for waste processing.